GAMBLING IN MALAYSIA: ISSUES, PROBLEMS AND SOLUTIONS - Ang Siew Mun; Ang Siew Ching, (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
Gambling is a normal activity among many non-Muslim Malaysians, and especially the ethnic Chinese Malaysians (CM). In this paper, we asked 60 Malaysian youths if they had gambled before and 78.3% (N=47) had replied ‘yes’. This showed that gambling is quite an acceptable cultural behaviour but that it can lead to more serious repercussions if uncontrolled. Moreover, past research supported the observation that Malaysians do generally gamble more than their Asian counterparts. Not surprisingly then, a majority of these 60 young Malaysian respondents surveyed believed that gambling is an entertainment and only 28.3% (N=17) think that gambling is a harmful activity. In this paper, the respondents were also surveyed on their perception of loan sharks which is an issue loosely associated with gambling and/or gambling addiction. Due to local media reports on loan shark harassments of their borrowers, it was clear that most of the respondents viewed loan sharking negatively. On the other hand, this paper also argued that gambling as an addiction, a social problem, and a mental health disease have not been publicly or widely acknowledged by the Malaysian authorities even though the latest edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) by the American Psychological Association (APA) has classified gambling addiction as a kind of substance-related, addictive disorder. Finally, this paper also provided possible solutions to help curtail gambling addiction as a mental health disease, an addiction, and a social problem.